2022
DOI: 10.3390/agronomy12051082
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vitro Simultaneous Acclimatization and Rooting of In Vitro Propagated Tamarillo Plants (Solanum betaceum Cav.): Effect of the Substrate and Mineral Nutrition

Abstract: Plants propagated by seed do not ensure genetic uniformity and are sometimes infected with diseases. In Vitro micropropagation techniques are an alternative method to traditional cloning approaches for producing true-to-type and pathogen-free plants. However, due to the particularities of the in vitro environment, these plants face many challenges, often critical to their survival, to adapt to ex vitro conditions. In this context, four substrates and two types of mineral nutrition (quick-release (QRF) and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…From the three applied treatments (A1, A2, A3), in vitro rooting gave the best results, although no statistically significant differences were found. Previous work carried out in tamarillo showed that rooting can be achieved in a medium with the auxin IBA [22]. Rooting of hardened plantlets without the addition of exogenous auxin was also obtained by Waweru et al in Dovyalis caffra [23], as ex vitro rooting has been poorly studied in Solanum.…”
Section: Axillary Shoot Proliferation and Acclimatizationmentioning
confidence: 99%
“…From the three applied treatments (A1, A2, A3), in vitro rooting gave the best results, although no statistically significant differences were found. Previous work carried out in tamarillo showed that rooting can be achieved in a medium with the auxin IBA [22]. Rooting of hardened plantlets without the addition of exogenous auxin was also obtained by Waweru et al in Dovyalis caffra [23], as ex vitro rooting has been poorly studied in Solanum.…”
Section: Axillary Shoot Proliferation and Acclimatizationmentioning
confidence: 99%
“…Simultaneous rooting and acclimatization of in vitro-produced plantlets represent a promising and efficient approach to plant production [11]. This innovative technique offers several advantages, including a reduction in labor and time required for plantlet production, and therefore, lowered costs, as well as enhanced survival rates during the transfer to ex vitro conditions [12]. The approach is particularly effective if performed with the use of light-emitting diodes (LEDs).…”
Section: Introductionmentioning
confidence: 99%